Pengaruh Green Marketing terhadap Purchase Intention (Studi pada Mahasiswa di UNISMA Angkatan 2021) - Jannah, Lailatul; Hidayati, Nur; Mustapita, Arini Fitria (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to find out; The Influence of Green Marketing on Purchase Intention. The type of research used is quantitative research with survey methods. The sample in this study was 101 respondents who were students at the Islamic University of Malang. The data collection method used in this research is by distributing questionnaires directly. The data analysis used is descriptive analysis and SEM-PLS analysis. The research results show that Green Marketing has a significant effect on Purchase Intention. It can be concluded that environmentally friendly marketing strategies have an important role in influencing consumers' intentions to purchase products.  Keywords: Green Marketing, and Purchase Intention